Family Financial Management Education as an Effort to Reduce Dependence on “Bank Tongol” in Sadran Puton Hamlet - Al Mu’ta’zim, M. Tsany; Safira, Seena; Sofiyani, Anisa; Safira, Vina Aulia; Atmarini, Resti; Susiatmi, Sandi Ari; Kholidah, Nur (Urecol Journal. Part B: Economics and Business, 2025)
The dependence of rural communities on informal financial institutions, such as "bank tongol," remains a serious obstacle to building household economic resilience. This high-interest lending practice persists due to limited access to formal financial institutions and low levels of financial literacy. Sadran Puton Hamlet is one of the areas affected by this issue. Through the Community Service Program (KKN), financial management education was provided to 20 married couples to reduce reliance on informal loans. The materials covered included budgeting, financial recordkeeping, emergency funds, and an introduction to Islamic financing. The program results showed that participants created more structured, prioritized family financial plans, reducing their tendency to borrow from banks. This education is expected to be a first step toward financial independence and strengthening household economic resilience.